2015
DOI: 10.1021/acs.nanolett.5b01810
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Neurite Outgrowth by Intracellular Stimulation

Abstract: Electrical stimulation through direct electrical activation has been widely used to recover the function of neurons, primarily through the extracellular application of thin film electrodes. However, studies using extracellular methods show limited ability to reveal correlations between the cells and the electrical stimulation due to interference from external sources such as membrane capacitance and culture medium. Here, we demonstrate long-term intracellular electrical stimulation of undamaged pheochromocytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…As CVDgrown Si nanowires have high-aspect-ratios (<10 3 ) and are sufficiently rigid to be mechanically manipulated, their nanometer scale diameters and high-aspect-ratios allow them to access the interiors of living cells without an external force for penetration. Previous studies have shown that CVD-grown vertical nanowires spontaneously penetrate the cell membrane when cells are placed on top of the nanowires [26][27][28][29][30][31] . The biocompatibility of small diameter nanowires is a critical element for the in situ study of cellular processes of living cells 26 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As CVDgrown Si nanowires have high-aspect-ratios (<10 3 ) and are sufficiently rigid to be mechanically manipulated, their nanometer scale diameters and high-aspect-ratios allow them to access the interiors of living cells without an external force for penetration. Previous studies have shown that CVD-grown vertical nanowires spontaneously penetrate the cell membrane when cells are placed on top of the nanowires [26][27][28][29][30][31] . The biocompatibility of small diameter nanowires is a critical element for the in situ study of cellular processes of living cells 26 .…”
Section: Resultsmentioning
confidence: 99%
“…By arranging the gold pads required for catalyzing the nanowires, we were able to position the nanowires with an optimum electrode pitch (110 µm) and dimensions for recording individual cells. For electrode fabrication, we used a top-down process with a CMOS device described in our previous reports 31,32 (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations